Ethnopharmacological survey of six medicinal plants used in the traditional treatment of urinary tract infections and other infectious diseases - ASSOGBA, Phénix; DOUGNON, Tamègnon Victorien; Agbodjento, Eric; AKOTEGNON, Rémi (My University, 2021)
Benin has attractive ethnobotanical potential with a vast diversity of medicinal plants widely used to treat human diseases. Urinary tract infections are among the diseases traditionally treated by medicinal plants. Mangifera indica, Bridelia ferruginea, Alstonia boonei, Morodora myristica, Xylopia aethiopica and Zanthoxylum zantoxyloides are six plants used in the traditional treatment of urinary infections in Benin. The general objective of this study was to identify the ethnopharmacological uses of these six plants used in traditional medicine in South Benin. To this end, an ethnopharmacological survey was conducted using the semi-structured interview method among herbalists in the markets of South Benin. The ethnobotanical data collected were analyzed using the use-value, the informant consensus factor and the medicinal plant fidelity index. A total of 98 herbalists participated in this study. The six plants studied were involved in 15 different diseases divided into seven disease categories. The most mentioned disease categories are infectious diseases, blood and digestive diseases. Malaria, ulcers, anemia and urinary tract infections are the pathologies most commonly treated by these plants. Informants agreed on the use of these plants in these disease categories. Bark, leafy stems and roots are the parts of the plants most used to treat diseases. Decoction and maceration are the two main methods of preparation, and the oral and cutaneous routes are the main routes of administration. These data constitute ethnopharmacological documentation that can be used for further pharmacological and toxicological studies.
Keywords: Medicinal plants; Ethnopharmacological use; Infectious diseases; Malaria and Anemia